Asteraceae Plants as Sources of Compounds Against Leishmaniasis and Chagas Disease - Moraes Neto, Roberval Nascimento; Setúbal, Ruth Flávia Barros; Higino, Taciana Mirely Maciel; Brelaz-de-Castro, Maria Carolina Accioly; da Silva, Luís Cláudio Nascimento; Aliança, Amanda Silva dos Santos (Frontiers in Pharmacology, 2019)
Leishmaniasis and Chagas disease cause great impact on social and economic aspects of people living in developing countries. The treatments for these diseases are based on the same regimen for over 40 years, thus, there is an urgent need for the development of new drugs. In this scenario, Asteraceae plants (a family widely used in folk medicine worldwide) are emerging as an interesting source for new trypanocidal and leishmanicidal compounds. Herein, we provide a non-exhaustive review about the activity of plant-derived products from Asteraceae with inhibitory action toward Leishmania spp. and T. cruzi. Special attention was given to those studies aiming the isolation (or identification) of the bioactive compounds. Ferulic acid, rosmarinic acid, and ursolic acid (Baccharis uncinella DC.) were efficient to treat experimental leishmaniasis; while deoxymikanolide (Mikania micrantha) and (+)-15-hydroxy-labd-7-en-17-al (Aristeguietia glutinosa Lam.) showed in vivo anti-T. cruzi action. It is also important to highlight that several plant-derived products (compounds, essential oils) from Artemisia plants have shown high inhibitory potential against Leishmania spp., such as artemisinin and its derivatives. In summary, these compounds may help the development of new effective agents against these neglected diseases.